A titanium-based porous coordination polymer as a catalyst for chemical fixation of CO2. Issue 19 (26th April 2017) - Du, Ya; Yang, Haishen; Wan, Shun; Jin, Yinghua; Zhang, Wei
Abstract : We report the synthesis of a porous coordination polymer consisting of titanium alkoxide linkages and its application in gas adsorption/separation and catalytic conversion of CO2 to cyclic carbonates. Abstract : A novel type of porous coordination polymer with titanium alkoxide linkages (Ti-PCP ) was successfully constructed through reaction of a 1, 3-diol-substituted shape-persistent arylene–ethynylene macrocycle with Ti(O i Pr)4 . The polymer exhibits a high Brunauer–Emmett–Teller (BET) surface area (1029 m 2 g −1 ) and good adsorption selectivity for CO2 over N2 . With n -Bu4 NBr as a co-catalyst, Ti-PCP can serve as a highly efficient catalyst to convert CO2 into cyclocarbonates through the cycloaddition reaction with epoxides under mild conditions. This framework-based heterogeneous catalyst not only has excellent catalytic activity, but also can be recycled and reused many times with easy product separation, thus showing its great potential for industrial applications as a green catalyst. With high uptake of CO2 and catalytic ability to convert CO2 to useful chemical compounds, this type of porous polymer with embedded catalytic centers could have important applications to solve environmental problems regarding post-combustion CO2 capture and conversion.